Evaluation Of Different Varieties Mixture Of Fruit Peel For Its Potential As A Functional Food. - Khatun, Mst Sharmin; Kanti Das, Sreemoy; Hossain, Arif; Gousuddin, Mohammad (Journal of Neonatal Surgery, 2025)
Introduction: Functional foods not only provide essential nutrition but also offer additional health benefits that enhance overall well-being and reduce illness risk. This research explores the potential of utilizing a blend of fruit peels from durian (the king of fruits), mata kuching (cats eye fruit), dragon fruit (pitaya), mangosteen (the queen of fruits), and rambutan as natural food ingredients. These peels are rich in flavonoids, phenols, alkaloids, sugars, and phytosterols, which exhibit antioxidant, antihistamine, antidepressant, and antimicrobial properties. Additionally, using fruit peels contributes to reducing food waste. Such beneficial and budget-friendly foods can be easily integrated into diets without the need for supplements or medications. Method: Peels from each fruit were collected, washed, dried, and ground into a fine powder. The powders were blended in equal ratios to create a fruit peel mixture (FPM). Bioactive compounds were extracted using a 70:30 ethanol-water solvent, and phytochemical analyses were conducted to evaluate anti-ulcer, antihistamine, antidepressant, and antioxidant activities through DPPH assays. Nutritional composition, including fiber, fat, protein, and carbohydrates, was determined using standard methods. Results: The combined peel mixture of Durio zibethinus (durian), Nephelium lappaceum L. (Rambutan), Selenicereus undatus (dragon fruit), Euphoria malaiense (Mata Kuching), and Garcinia mangostana L. (mangosteen) were examined for its physicochemical properties and functional food potential. No toxicity was observed in acute tests at 72 mg extract or even at higher doses (500 mg/kg and 1000 mg/kg) during sub-acute evaluations compared to control animals. The extract demonstrated significant bioactive activity, particularly in anti-ulcer, antihistamine, antidepressant, and antioxidant properties, indicating its potential as a safe and effective functional food component beneficial for health promotion and the prevention of oxidative stress-related diseases. Conclusion: The combined peels of rambutan, Mata Kuching, durian, mangosteen, and dragon fruit suggest promising potential as a functional food. The sample proved to be non-toxic in both chronic and sub-chronic tests. The notable antioxidant, anti-ulcer, antihistamine, and antidepressant effects highlight its therapeutic relevance. Future studies should focus on investigating the mechanisms of action and determining appropriate dosages for food applications and pharmaceutical use...